Interdisciplinary care practices through a multiprofessional residence in diabetes (Research, Society and Development, 2020)
This study describes interdisciplinary care practices developed in a multiprofessional residence in diabetes. This is a descriptive study carried out in an Endocrinology and Diabetes Service. Data collection took place from September to December 2020, using a semi-structured form and direct observation. The sample consisted of 16 healthcare workers and support professionals. The data were analyzed descriptively. The results show that the multiprofessional residency program in diabetes is an ongoing, promising and innovative health education strategy that seeks to aggregate theory and practice during the exercise of in-service activities, and enables the sharing of information in the multidisciplinary team, generating integrated, interdisciplinary, and holistic healthcare. Thus, it is concluded that interdisciplinary care practices enable, in addition to specific training, the expansion of specialized diabetes care in the three levels of healthcare, subsidizing improvements in the quality of life of patients and the training of qualified professionals for the job market.